Integration of the interactive smart board in teaching english as a second language for the development of vocabulary skills in students of higher education institutions - Vornyk, Mariya (Journal of Education, Health and Sport, 2025)
The article explores the specifics of integrating the interactive smart board into the educational process of higher education institutions with the aim of developing vocabulary skills in students learning English as a Second Language (ESL). Theoretical approaches to the formation of lexical competence in university students are analyzed, and the didactic potential of interactive technologies in higher education is determined. The main stages of working with lexical material using the interactive smart board are characterized, as well as its impact on students’ motivation, autonomy, and communicative activity. The study concludes that the use of the interactive smart board is both appropriate and effective as a means of intensifying English language instruction in higher education institutions.